2010
DOI: 10.1016/j.matchemphys.2010.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of different ZnO nanostructures by modified PVD process and potential use for dye-sensitized solar cells

Abstract: a b s t r a c t Different ZnO nanostructures were synthesized by physical vapor deposition on glass-ITO substrates. Nanowires and nanosheets were obtained by a single step process using gold nanoparticles and gold thin films as catalyst. 3D nanoarchitectures were obtained by a two-step modified process; the morphology of these structures depends on the catalyst used for the second deposition: gold nanoparticles or zinc acetate seeds. All the nanostructures were characterized by SEM and TEM analyses, which show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…A metal-organic chemical vapour (MOCVD) process was also used to prepare 2D ZnO nanowalls on GaN/Al 2 O 3 substrates [47]. Physical vapour deposition (PVD) was used to synthesise ZnO nanosheets for dye solar cell applications [48] High-pressure pulsed laser deposition (PLD) method was also used for growing 2D ZnO nanowalls. In addition, it was found that the lattice parameter of the substrate used for the growth of 2D ZnO plays a crucial rule in the growing process.…”
Section: Miscellaneous Methods For Preparing 2d Znomentioning
confidence: 99%
See 1 more Smart Citation
“…A metal-organic chemical vapour (MOCVD) process was also used to prepare 2D ZnO nanowalls on GaN/Al 2 O 3 substrates [47]. Physical vapour deposition (PVD) was used to synthesise ZnO nanosheets for dye solar cell applications [48] High-pressure pulsed laser deposition (PLD) method was also used for growing 2D ZnO nanowalls. In addition, it was found that the lattice parameter of the substrate used for the growth of 2D ZnO plays a crucial rule in the growing process.…”
Section: Miscellaneous Methods For Preparing 2d Znomentioning
confidence: 99%
“…It was found that controlling the experiment parameters results in significant changes in the morphology of the prepared 2D ZnO. Parameters such as substrate lattice mismatch between the substrate and the film will result in the modification of the ZnO structure [48]. The morphology of ZnO structures can be modified by adding salts, such as KCl and CH 3 COONH, to the electrolyte in the electrodeposit method [41].…”
Section: The Crystal Structural and The Morphology Of The 2d Znomentioning
confidence: 99%
“…Physical vapor deposition (PVD) is a technique for the preparation of metal oxide nanostructures that has been optimized during recent years [29][30][31]. In this case, The ZnO nanowires can grow according to two different mechanisms: vapor-liquid-solid or vapor-solid, depending on both the source material and destination growth sites [30,31].…”
Section: Physical Vapor Depositionmentioning
confidence: 99%
“…In this case, The ZnO nanowires can grow according to two different mechanisms: vapor-liquid-solid or vapor-solid, depending on both the source material and destination growth sites [30,31]. The PVD system consists of a tubular furnace with regulable temperature which is connected to a rotary vacuum pump in order to control the pressure inside the furnace.…”
Section: Physical Vapor Depositionmentioning
confidence: 99%
See 1 more Smart Citation